KIDNEY, LIVER AND HEART DONATION AND TRANSPLANTATION IN THE REPUBLIC OF SERBIA FOR THE PERIOD 2010-2016 - Vlacic, Sandra; Nikolic, Aleksandra; Sipetic, Sandra (HEALTH CARE, 2021)
Introduction/aim: It is estimated that in 2017, 139,024 solid organ transplants (kidney, liver, heart, lungs, pancreas, small intestine) were performed, which is only 10% of global needs. The aim of this descriptive study was to analyze the frequency of donation and transplantation of solid organs (kidney, liver and heart) in Republic of Serbia for the period 2010-2016.Methods: Data on the number of donors and the number of transplanted organs in Serbia, for the period 2010-2016, were obtained from the Annual reports of the Ministry of Health Republic of Serbia -Directorate of Biomedicine. Data on the population of Serbia were taken from the 2011 census. Proportions and rates were used in the analysis of the obtained data.Results: In Republic of Serbia, average donation rate, for the period 2010-2016, was 3.7 pmp. During the last seven years, among all performed transplants from deceased donors, the largest percentage were transplants of kidneys (78.3%), followed by liver (16.9%) and heart (4.8%). In transplant centers in Serbia, for the period 2010-2016, 537 kidney transplants were performed, 328 from deceased and 209 from living donors. The average rate of kidney transplants for the seven-year period was 10.6 pmp, or 4.1 pmp for living donors and 6.5 pmp for deceased donors. In the same period, 71 liver transplants and 20 heart transplants from deceased donors were performed, and the average transplant rates were 1.4 pmp and 0.4 pmp.Conclusion: In the observed period, the lowest rates of kidney transplantation from living and deceased donors, as well as liver and heart from deceased donors, were recorded in Serbia, in relation to all other European countries. The field of organ transplantation in Serbia is legally regulated by the Law on Human Organ Transplantation. Conditions for achieving quality standards and safety of human organs for transplantation have been determined by this law, as well as working conditions and ways of organizing the health system to ensure optimal organ transplantation and provision, high level of protection of human health, as well as respect priority interests for the preservation of life and health and protection of basic human rights and dignity of organ donors and recipients. Special emphasis should be placed on educating the population and health care workers about the importance of organ donation.
Keywords: transplantation, donation, kidney, heart, liver